Personnel callout system - Ingvar Karl Þorsteinsson (2005)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri This dissertation is about a final year project by Ingvar Karl Þorsteinsson, a student in the Department of Computer Science at the University of Akureyri. This aim of this document is to give a report about the project in details. The name of the project is Personnel Callout System. It is designed specifically for Súlur, the rescue unit in Akureyri. The system is designed to organize members in the rescue unit into callout groups, and to make callouts using mobile phones of the members, based on groups. The report starts giving general information about the unit, their current practices and the problems they are having in data redundancy and inconsistency due to the use of many systems storing data. Requirements of the project were analyzed and are stated, followed by a design that addresses the requirements. The tools and development environments are given a brief discussion followed by detailed information about the implementation and evaluation. In the end of the report, there is a personal review of the project stating the conclusion.